Clinical Guideline Highlights for the Hospitalist: Clostridium difficile Infections in Children. Issue 2 (23rd October 2019) - Rogers, Amanda; ElKadri, Abdul
Abstract : GUIDELINE TITLE: Clinical Practice Guidelines for Clostridium difficile Infection in Adults and Children: 2017 Update by the Infectious Diseases Society of America (IDSA) and Society for Healthcare Epidemiology of America (SHEA). RELEASE DATE: February 15, 2018 PRIOR VERSIONS: : Cohen SH, Gerding DN, Johnson S, et al; Society for Healthcare Epidemiology of America; Infectious Diseases Society of America. Clinical practice guidelines for Clostridium difficile infection in adults: 2010 update by the Society for Healthcare Epidemiology of America (SHEA) and the Infectious Diseases Society of America (IDSA). Infect Control Hosp Epidemiol . 2010; 31:431‐55. Gerding DN, Johnson S, Peterson LR, et al. Clostridium difficile‐associated diarrhea and colitis. Infect Control Hosp Epidemiol 1995;16:459‐477. DEVELOPER: IDSA and SHEA. FUNDING SOURCE: Support for this guideline was provided by the IDSA and SHEA. TARGET POPULATION: Children and adults with Clostridium difficile infections.